Annual assessment of Echinococcus multilocularis surveillance reports submitted in 2018 in the context of Commission Regulation (EU) No 1152/2011. (7th December 2018) - ,; Ciubotaru, Ramona Mihaela; Oyedele, Joshua; Zancanaro, Gabriele
Abstract: This report is part of the ` Echinococcus multilocularis surveillance' scientific reports which are presented annually by EFSA to the European Commission and are intended to assess the sampling strategy, data collection and detection methods used by Finland, Ireland, Malta, the United Kingdom (UK) and Norway in their respective surveillance programmes. The surveillance programmes of these five countries were evaluated by checking the information submitted by each of them and verifying that the technical requirements laid down in Regulation (EU) No 1152/2011 were complied. The information was divided in four different categories for assessment: the type and sensitivity of the detection method, the selection of the target population, the sampling strategy and the methodology. For each category, the main aspects that need to be considered in order to accomplish the technical requirements of the legislation were checked against compliance of several criteria. All of the countries participating in this surveillance (Finland, the UK, Norway, Malta and Ireland) succeeded in the fulfilment of the technical legal requirements foreseen in Regulation (EU) No 1152/2011 concerning these four different categories. Northern Ireland (UK) fulfils those requirements only when assuming a diagnostic test sensitivity value of 0.99, which is higher than the sensitivity value suggested by EFSA (conservative value of 0.78). None of the five countries recorded positive samples in the 12‐month reporting period.